Roles of YcfR in biofilm formation in Salmonella typhimurium ATCC 14028 - Kim, Seul I.; Yoon, Hyunjin (Molecular Plant-Microbe Interactions, 2019)
An increasing number of foodborne diseases are currently attributable to farm produce contaminated with enteric pathogens such as Salmonella enterica. Recent studies have shown that a variety of enteric pathogens are able to colonize plant surfaces by forming biofilms and thereby persist for long periods, which can subsequently lead to human infections. Therefore, biofilm formation by enteric pathogens on plants poses a risk to human health. Here, we deciphered the roles of YcfR in biofilm formation by Salmonella enterica. YcfR is a putative outer membrane protein associated with bacterial stress responses. The lack of YcfR facilitated the formation of multicellular aggregates on cabbage leaves as well as glass surfaces while reducing bacterial motility. ycfR deletion caused extensive structural alterations in the outer membrane, primarily in lipopolysaccharides, outer membrane proteins, cellulose, and curli fimbria, thereby increasing cell surface hydrophobicity. However, the absence of YcfR rendered Salmonella susceptible to stressful treatments, despite the increased multicellular aggregation. These results suggest that YcfR is an essential constituent of Salmonella outer membrane architecture and its absence may cause multifaceted structural changes, thereby compromising bacterial envelope integrity. In this context, YcfR may be further exploited as a potential target for controlling Salmonella persistence on plants.
Keywords: Bacterial Outer Membrane Proteins; Biofilms; Humans; Plants; Salmonella typhimurium